Pay for performance in the states - Ingraham, Patricia W. (1993)
This research examines pay performance systems in the American states. The author's survey of those states with current pay for performance legislation finds that not all states with programs on the books have operational systems, nor do those with operational programs fund them consistently. A majority of personnel directors find the systems to be effective, but implementation problems occurred in nearly every state. The author suggests that for future policy expansion and diffusion a set of decision criteria linking policy expectations with personnel system's capability and support is necessary
Keywords: Performance awards - United States; Merit pay - United States; Bureaucracy - United States; Civil service - United States